Interpretive Guidance of the International Committee of the Red Cross on the Notion of Direct Participation in Hostilities: pro et contra - V. N. Rusinova (Московский журнал международного права, 2011)
Among the main advantages of the Guidance the author distinguishes a classification of persons in non-international armed conflicts, use of the purpose as a defining feature of the notion of “hostilities”, inclusion of unlawful attacks against the civilian purposes in this notion, application of the principle of military necessity as one of the restrictions of the use of force. Several issues of the Guidance are subjected to criticism: a limited scope of application of the minimum threshold requirement to the harm, a dogmatic position on absolute impossibility of qualification of attacks on the persons under authority of a party to the conflict as “hostilities”, a requirement of existence of a link between a civilian and a party to the conflict, elusion from qualification of general planning and leadership. Finally, the author comes to the conclusion that the process of clarification of the notion “direct participation in hostilities” should be continued.